Preclinical Characterization of a Novel Monoclonal Antibody NEO-201 for the Treatment of Human Carcinomas - Fantini, Massimo; David, Justin M.; Saric, Olga; Dubeykovskiy, Alexander; Cui, Yongzhi; Mavroukakis, Sharon A.; Bristol, Andrew; Annunziata, Christina M.; Tsang, Kwong Y.; Arlen, Philip M. (Frontiers in Immunology, 2018)
NEO-201 is a novel humanized IgG1 monoclonal antibody (mAb) that was derived from an immunogenic preparation of tumor-associated antigens from pooled allogeneic colon tumor tissue extracts. It was found to react against a variety of cultured human carcinoma cell lines, and was highly reactive against the majority of tumor tissues from many different carcinomas, including colon, pancreatic, stomach, lung, and breast cancers. NEO-201 also exhibited tumor specificity, as the majority of normal tissues were not recognized by this antibody. Functional assays revealed that treatment with NEO-201 is capable of mediating both antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) against tumor cells. Furthermore, the growth of human pancreatic xenograft tumors in vivo was largely attenuated by treatment with NEO-201 both alone and in combination with human peripheral blood mononuclear cells (PBMC) as an effector cell source for ADCC. In vivo biodistribution studies in human tumor xenograft-bearing mice revealed that NEO-201 preferentially accumulates in the tumor but not organ tissue. Finally, a single-dose toxicity study in non-human primates demonstrated safety and tolerability of NEO-201, as a transient decrease in circulating neutrophils was the only related adverse effect observed. These findings indicate that NEO-201 warrants clinical testing as both a novel diagnostic and therapeutic agent for the treatment of a broad variety of carcinomas.